PENGARUH KURS DOLLAR, INFLASI DAN JUMLAH PRODUKSI PADI TERHADAP IMPOR BERAS INDONESIA TAHUN 1991–2019 - Estyawan, Made Adhi Padma; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.02.TAHUN.2024, 2024)
Even though Indonesia is one of the largest rice producing countries in the world, Indonesia still imports rice. The purpose of this study was to determine and analyze the simultaneous and partial effect of the US dollar exchange rate, inflation and rice production on Indonesian rice imports from 1991 to 2019. The study was conducted in Indonesia, the number of observations was 29 years. The data used is secondary data. The analysis technique used is multiple linear regression analysis, using Eviews software. The results showed that the US dollar exchange rate, inflation, and rice production simultaneously had a significant effect on Indonesian rice imports from 1991 to 2019. The US dollar exchange rate partially had no significant effect on Indonesian rice imports from 1991 to 2019. Inflation was partial positive and significant effect on Indonesian rice imports from 1991 to 2019. Partial rice production did not significantly affect Indonesian rice imports from 1991 to 2019. It is hoped that the government can pay more attention to the agricultural sector by making policies in an effort to encourage increasing domestic rice and rice production in order to achieve food self-sufficiency, so that imports can be suppressed and achieve a balance of domestic trade balance.